A Novel Age-Related Circular RNA Circ-ATXN2 Inhibits Proliferation, Promotes Cell Death and Adipogenesis in Rat Adipose Tissue-Derived Stromal Cells - Song, Xing-Hui; He, Ning; Xing, Yue-Ting; Jin, Xiao-Qin; Li, Yan-Wei; Liu, Shuang-Shuang; Gao, Zi-Ying; Guo, Chun; Wang, Jia-Jia; Huang, Ying-Ying; Hu, Hu; Wang, Lin-Lin (Frontiers in Genetics, 2021)
Adipose tissue-derived stromal cells are promising candidates investigating the stem cell-related treatment. However, their proportion and utility in the human body decline with time, rendering stem cells incompetent to complete repair processes in vivo. The involvement of circRNAs in the aging process is poorly understood. Rat subcutaneous adipose tissue from 10-week-old and 27-month-old rats were used for hematoxylin and eosin (H&E) staining, TUNEL staining, and circRNA sequencing. Rat adipose tissue-derived stromal cells were cultured and overexpressed with circ-ATXN2. Proliferation was examined using xCELLigence real-time cell analysis, EdU staining, and cell cycle assay. Apoptosis was induced by CoCl2 and examined using flow cytometry. RT-PCR assay and Oil Red O staining were used to measure adipogenesis at 48 h and 14 d, respectively. H&E staining showed that the diameter of adipocytes increased; however, the number of cells decreased in old rats. TUNEL staining showed that the proportion of apoptotic cells was increased in old rats. A total of 4,860 and 4,952 circRNAs was detected in young and old rats, respectively. Among them, 67 circRNAs exhibited divergent expression between the two groups (fold change ≥ 2, p ≤ 0.05), of which 33 were upregulated (49.3%) and 34 were downregulated (50.7%). The proliferation of circ-ATXN2-overexpressing cells decreased significantly in vitro, which was further validated by xCELLigence real-time cell analysis, EdU staining, and cell cycle assay. Overexpression of circ-ATXN2 significantly increased the total apoptotic rate from 5.78 ± 0.46% to 11.97 ± 1.61%, early apoptotic rate from 1.76 ± 0.22% to 5.50 ± 0.66%, and late apoptosis rate from 4.02 ± 0.25% to 6.47 ± 1.06% in adipose tissue-derived stromal cells. Furthermore, in circ-ATXN2-overexpressing cells, RT-PCR assay revealed that the expression levels of adipose differentiation-related genes PPARγ and CEBP/α were increased and the Oil Red O staining assay showed more lipid droplets. Our study revealed the expression profile of circRNAs in the adipose tissue of old rats. We found a novel age-related circular RNA—circ-ATXN2—that inhibits proliferation and promotes cell death and adipogenesis in rat adipose tissue-derived stromal cells.